High performance and enhanced stability of Mn-Co3V2O8 coral-like structure for supercapacitor applications - Venkatesan, Sethuraman; Rajkumar, Palanisamy; Radhika, Govindaraju; Iyer, Maalavika S.; Manigandan, Ramadoss; Rajaiah, Dhilip Kumar; Radhakrishnan, S.; Raman, Sasikumar; Marimuthu, Senthilkumaran; Kim, Jinho (ACS Applied Energy Materials, 2025)
This study explores Mn-doped Co3V2O8 as a promising electrode material for high-performance supercapacitors. Mn doping significantly enhances the electrochemical properties of Co3V2O8, resulting in improved specific capacitance and cycling stability. Structural characterization reveals a coral-like morphology that increases the active sites and facilitates efficient charge transport and ion diffusion. Electrochemical tests show an impressive specific capacitance of 2352 F g(-1) in 2 M KOH at 1 A g(-1). For the assembled MCV5//AC asymmetric supercapacitor device, it has a high capacitance retention of 87.6% and a high Coulombic efficiency of 96% over 5000 cycles. The developed asymmetric MCV5/AC supercapacitor device achieved an energy density of 45 Wh kg(-1) and a power density of 750 W kg(-1). These findings establish Mn-doped Co3V2O8 as a durable and efficient electrode material, offering valuable insights into the relationship between the morphology and electrochemical performance. This work provides a foundation for the development of advanced materials for sustainable energy storage applications
Keywords: Co3V2O8; Electrode material; Energy storage; stability; supercapacitor